2017
DOI: 10.25258/ijpqa.v8i04.10546
|View full text |Cite
|
Sign up to set email alerts
|

Cyclamen persicum: Methanolic Extract Using Gas Chromatography-Mass Spectrometry (GC-MS) Technique

Abstract: Cyclamen was traditionally classified in the family Primulaceae, was reclassified in the subfamily Myrsinoideae within the family Primulaceae. The objective of this study was analysis of the secondary metabolite products. Bioactives are chemical compounds often referred to as secondary metabolites. Thirty eight bioactive compounds were identified in the methanolic extract of Cyclamen persicum. The identification of bioactive chemical compounds is based on the peak area, retention time molecular weight and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The fruit is used in nearly every home in the tropics, mainly to flavour food, but also to prepare drinks and for a variety of medicinal applications. The antifungal activity of the plant have been attributed to the presence of monoterpenes and the plant is currently used as a fungicide for citrus fruit crop, and it has also been suggested that the plant may be a potential candidate used for the protection of food and feeds from toxigenic fungal growth as well as their aflatoxin contamination [1][2][3][4][5][6][7][8][9] . It has been traditionally used in the management of several diseases and has the prospects of being developed into useful drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit is used in nearly every home in the tropics, mainly to flavour food, but also to prepare drinks and for a variety of medicinal applications. The antifungal activity of the plant have been attributed to the presence of monoterpenes and the plant is currently used as a fungicide for citrus fruit crop, and it has also been suggested that the plant may be a potential candidate used for the protection of food and feeds from toxigenic fungal growth as well as their aflatoxin contamination [1][2][3][4][5][6][7][8][9] . It has been traditionally used in the management of several diseases and has the prospects of being developed into useful drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The GC-MS analysis of fractions 19–26 (25–30% EtOAc in n -hexane as eluent) showed the presence of two peaks as shown in the chromatogram ( Figure 2 ). By comparing the mass spectra ( Figure 3 ) of the composition at the retention time of 4 min with the NIST library, compound 4 was identified as a pregnane derivative named as 3,9-epoxypregn-16-ene-14,20-diol,7,11,18-triacetoxy-3-OCH 3 , previously reported from the GC-MS of CH 3 OH extract of Cyclamen persicum [ 39 ].…”
Section: Resultsmentioning
confidence: 94%
“…Because of its solvent-free nature and low toxicity, plant-based nanoparticle production has gained popularity in recent years. Furthermore, their synthesis is much quicker and less costly [9,10]. Bacteria, yeast, and fungi have been demonstrated to produce AgNP during the biosynthetic process [11,13].…”
Section: Introductionmentioning
confidence: 99%